The Impact of Religiosity on Work Stress Among Teachers in SDN Krembung District: Dampak Religiusitas terhadap Stres Kerja di Kalangan Guru SDN Kecamatan Krembung - Muda Dini, Novia Dewi; Mariyati, Lely Ika (Indonesian Journal of Education Methods Development, 2023)
This quantitative correlational study aims to examine the relationship between religiosity and work stress among teachers in SDN Krembung District. The sample consisted of 148 teachers selected using incidental sampling. Data analysis included normality test, linearity test, and simple linear regression analysis using the SPSS 20 for Windows program. The findings revealed a negative relationship between religiosity and work stress among SDN teachers in Krembung District, with a significant correlation coefficient of -0.205 (p = 0.006 < 0.05). These results support the researcher's hypothesis, indicating that higher levels of religiosity are associated with lower work stress. However, it is important to note that religiosity explains only 3.5% of the variation in work stress, with 96.5% influenced by other factors not examined in this study. The limitations of this research include the pandemic-related time constraints and the focus solely on the variable of religiosity without considering other potential correlates of work stress. The implications of this study suggest the importance of promoting religiosity among teachers through activities such as collective prayers before classes, weekly istiqosah (spiritual gathering), and annual nature contemplation. These activities can help reduce work stress and inspire new teaching ideas, benefiting both teachers and schools in SDN Krembung District. Highlight: Negative relationship: The study found a negative relationship between religiosity and work stress among teachers in SDN Krembung District. Sample: The study included 148 teachers from SDN in Krembung sub-district, providing valuable insights into the local context. Implications: Promoting religiosity through collective prayers, istiqosah sessions, and nature contemplation can help reduce work stress and generate new teaching ideas for teachers in SDN Krembung District. Keyword: Religiosity, Work Stress, Teachers, Negative Relationship, SDN Krembung District